2021
DOI: 10.3390/jpm11030230
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Similarities in Neuropathy in Type 1 and 2 Diabetes: A Systematic Review

Abstract: Background: Diabetic neuropathy is defined as the dysfunction of the peripheral nervous system in diabetic patients. It is considered a microvascular complication of diabetes mellitus. Its presence is associated with increased morbidity and mortality. Although several studies have found alterations at somatic motor, sensory levels and at the level of autonomic nervous system in diabetic patients, there is not a systematic approach regarding the differences in neuropathy between the major variants of diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 87 publications
(185 reference statements)
1
15
0
1
Order By: Relevance
“…Diabetes, as a disease characterized by hyperglycemia, is related to diverse complications, including cardiovascular disease, stroke, kidney failure, neuropathy, retinopathy, and amputation (Al-Sofiani et al, 2019;Lau et al, 2019;Buades et al, 2021;Sempere-Bigorra et al, 2021;Milluzzo et al, 2021;O'neill et al, 2017). It is reported that diabetes can be divided into three types: Gestational diabetes, type 1 diabetes (T1D), and type 2 diabetes (T2D) (Xiang et al, 2018).…”
Section: Diabetic Imagingmentioning
confidence: 99%
“…Diabetes, as a disease characterized by hyperglycemia, is related to diverse complications, including cardiovascular disease, stroke, kidney failure, neuropathy, retinopathy, and amputation (Al-Sofiani et al, 2019;Lau et al, 2019;Buades et al, 2021;Sempere-Bigorra et al, 2021;Milluzzo et al, 2021;O'neill et al, 2017). It is reported that diabetes can be divided into three types: Gestational diabetes, type 1 diabetes (T1D), and type 2 diabetes (T2D) (Xiang et al, 2018).…”
Section: Diabetic Imagingmentioning
confidence: 99%
“…There is also a link between the levels of ICAM-1 and diabetic neuropathy [22]. So, both CRP and soluble adhesion molecules can be considered as attractive early predictors of diabetic complications and therapeutic targets for diabetic patients [23].…”
Section: Similarly With Regards To Cell Adhesion Molecules a Linear Association Was Reported Between Elevations Of Icam-1 And Diabetic Rementioning
confidence: 99%
“…Diabetes mellitus (DM) describes a state of chronic hyperglycemia that affects more than 460 million individuals worldwide [ 1 ]. The number of patients with DM has been projected to rise to 700 million worldwide by 2045 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%